The Role of Treaties for The Avoidance of Double Taxation and Tax Evasion in Encouraging Foreign Investment in Iraq - kamal Anwer Yaba; Muhammad Hamad Razak (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In the last century, foreign investment attracted the attention of countries, as great competition prevailed among them, especially developing ones, to attract foreign investments, because the economies of these countries were in precarious position as the result of the constant fluctuation in the prices of oil resources. Consequently, the countries realized the necessity of enticing foreign investment as an alternative source of hard currency, and appreciated the effectiveness of foreign investment as a mechanism for achieving development, but due to the countries' adherence to the principle of tax sovereignty, and the inconsistency of their tax laws and regulations with global economic developments, they quickly collided with what is known as the problem of international double taxation. Which consists of subjecting the same income or money to the same tax or tax of the same type during the same period by more than one country, which would adversely affect the future of international economic relations, it also results in serious negative effects on the economies of countries, as international double taxation has become one of the most important problems that prevent the growth of international trade in general and foreign investments in particular. This has prompted the international community to adopt a number of bilateral and multilateral treaties to avoid double taxation and encouraging the international investment trends on the one hand, and combating tax evasion at the international level on the other hand.